Analisis Kinerja Keuangan Terhadap Perusahaan Merger Pada Bursa Efek Indonesia (Bei) - Fatmawati Fatmawati; Paula Agustina Sitorus; Ratih Kusumastuti (Student Research Journal, 2023)
Many companies carry out business combinations by way of mergers. The reason is because there are "additional benefits" that will be obtained or the company will be able to achieve faster growth than having to build its own business units. This study aims to analyze financial performance using financial statement ratios in a merger company, namely PT Ciputra Development Tbk. This research uses quantitative research methods. Quantitative data used were obtained from the Indonesia Stock Exchange www.idx.co.id and the company's website. In this study, we will discuss the ratios of financial statements that have a relationship with financial performance.